(untitled) (Advances in Systems Science and Applications, 2017)
Modern multipurpose Autonomous Underwater Vehicles (AUVs) represent the next generation of robotic systems with new technological tasks faced by researchers. One method of extending the functionality of the vehicle is installing tunnel thrusters in addition to the stern propulsion system. Thereby the vehicle becomes able to undertake both survey-style missions and low speed interactions with the environment. But the efficiency of the tunnel thruster depends strongly on the vehicle’s velocity, due to hydrodynamic aspects. The usual solution to this problem uses different control models and thrust allocation methods for these types of mission. A unified approach to thrust allocation is presented in this paper. The approach is based on solving the allocation problem by quadratic programming with variable constraints, depending on the velocity of the AUV and the thrusters’ angle of attack. The well-known implementation of active set method was used to model the proposed allocation method.